Regulation of Hippo-YAP signaling by insulin-like growth factor-1 receptor in the tumorigenesis of diffuse large B-cell lymphoma - Xiangxiang Zhou; Na Chen; Hongzhi Xu; Xiaoming Zhou; Jianhong Wang; Xiaosheng Fang; Ya Zhang; Ying Li; Juan Yang; Xin Wang (Journal of Hematology & Oncology, 2020)
Abstract Background Hippo-Yes-associated protein (YAP) signaling is a key regulator of organ size and tumorigenesis, yet the underlying molecular mechanism is still poorly understood. At present, the significance of the Hippo-YAP pathway in diffuse large B-cell lymphoma (DLBCL) is ill-defined. Methods The expression of YAP in DLBCL was determined in public database and clinical specimens. The effects of YAP knockdown, CRISPR/Cas9-mediated YAP deletion, and YAP inhibitor treatment on cell proliferation and the cell cycle were evaluated both in vitro and in vivo. RNA sequencing was conducted to detect dysregulated RNAs in YAP-knockout DLBCL cells. The regulatory effects of insulin-like growth factor-1 receptor (IGF-1R) on Hippo-YAP signaling were explored by targeted inhibition and rescue experiments. Results High expression of YAP was significantly correlated with disease progression and poor prognosis. Knockdown of YAP expression suppressed cell proliferation and induced cell cycle arrest in DLBCL cells. Verteporfin (VP), a benzoporphyrin derivative, exerted an anti-tumor effect by regulating the expression of YAP and the downstream target genes, CTGF and CYR61. In vitro and in vivo studies revealed that deletion of YAP expression with a CRISPR/Cas9 genome editing system significantly restrained tumor growth. Moreover, downregulation of IGF-1R expression led to a remarkable decrease in YAP expression. In contrast, exposure to IGF-1 promoted YAP expression and reversed the inhibition of YAP expression induced by IGF-1R inhibitors. Conclusions Our study highlights the critical role of YAP in the pathogenesis of DLBCL and uncovers the regulatory effect of IGF-1R on Hippo-YAP signaling, suggesting a novel therapeutic strategy for DLBCL.